Protocolo de consulta: descrição do processo de elaboração na comunidade quilombola indígena Sitio Conceição, Barcarena–Pará - CRAVO, José Roberto de Jesus da Silva (2021)
The conclusion work of Ethnodevelopment Bachelor degree presents the process of collective construction of the Consultation Protocol of the ranch Conceição – an Indigenous Quilombola Community located in the municipality of Barcarena, State of Pará - which had as its main purpose the confrontation and strengthening of social unit rights. Since the 1970s / 1980s, with the installation of the industrial complex called ALBRAS / ALUNORTE in Barcarena and the developmental actions imposed by CODEBAR (Companhia de Desenvolvimento de Barcarena), these rights have been utterly violated. The Indigenous Quilombola Community ranch Conceição suffered the impact of the developmental actions of the State and ALBRAS/ALUNORTE Company, suffered exclusion and displacement processes. But they were resistant, organized fights to return and retake the territory, as well as collective actions before the Public Prosecutor's Office, and, finally, to strengthen their struggle, the proposal to prepare our Protocol of Prior, Free and Informed Consultation, based on Convention 169 of the Organization International Labor Office -OIT. The elaboration of the protocol began in December 2017 and extends to the present moment. There were successive meetings in the form of workshops, lectures, seminars and meetings, moments of discussions and political strengthening of the community. The Protocol is in the final stage of submission for approval by the community, which will be led by the Ranch Conceição Indigenous Quilombola Community Association - ACOMQUISC will have a collective representative political instrument.